EVALUATION OF THE USE OF ANTIHYPERTENSIVE DRUGS IN OUTPATIENTS USING THE ATC/DDD METHOD AS A FORM OF IMPLEMENTATION OF SHARIA SERVICES AT THE PONCOL HEALTH CENTER UPTD - ibi, Nur Afni oktavia; Ramadhani, Azmi; nadia (Gamma Publishing, 2025)
Community Health Centers (Puskesmas) are basic health service facilities that organize health maintenance efforts, health improvement (promotive), disease prevention (preventive), disease healing (curative), and health recovery (rehabilitative), which are implemented in a comprehensive, integrated, and sustainable manner. Hypertension is defined as an increase in systolic blood pressure of more than 140 mmHg and an increase in diastolic blood pressure of more than 90 mmHg. The use of appropriate hypertension medication is one of the functions of successful hypertension treatment. There are 4 main characteristics in Islamic services, namely rabbaniyah, akhlaqiyah, waqi'iyah and insaniyah. What distinguishes Islamic health services from non-Islamic health services lies in the rabbaniyah characteristics, namely belief and submission of everything because of the will of Allah SWT. This study aims to determine the profile of antihypertensive drug use in outpatients at the Poncol Health Center UPTD in the 2024 period and to determine the ATC/DDD value in the evaluation of antihypertensive drug use in outpatients at the Poncol Health Center UPTD in the 2024 period. The results of the study showed that the antihypertensive drugs used at the Poncol Health Center UPTD in 2024 with an average quantity of use of, Amlodipine 87.83 DDD/1000 KPRJ, Candesartan 5.73 DDD/1000 KPRJ, Liaianopril 3.67 DDD/1000 KPRJ, Bisoprolol 1.83 DDD/1000 KPRJ, Hydrochlorothiazide 0.68 DDD/1000 KPRJ, Nifedipine 0.24 DDD/1000 KPRJ, Furosemide 0.09 DDD/1000 KPRJ, Valsartan 0.014 DDD/1000 KPRJ, Telmisartan 0.0037 DDD/1000 KPRJ, captopril 0.0023 DDD/1000 KPRJ. The most widely used drugs are Amlodipine and Candesartan.